A CLINICAL CASE OF HYDROALLONTOIS IN A PLEURIPAROUS NON-DESCRIPTIVE BUFFALO. - BALAMURUGAN, B; Reddy, YV PRIDHVIDHAR; JYOTHI, K (The Indian Journal of Animal Reproduction, 2020)
A 2nd parity, non-descriptive 8th month pregnant buffalo was presented to DVCC with the history of bilateral abdominal enlargement since 7-10 days. Had treatment history of dexamethasone, oxytetracycline. Had vaginal watery discharge since two days. Animal had anorexia and not taking water since two days. General clinical examination revealed dull and depressed, all the vital parameters were not within the normal range. Hence it is diagnosed as hydroallantois. Animal was stabilized with fluid therapy. On per- rectal examination revealed tough fluid filled uterus. On per-vaginal examination revealed cervix was dilated three fingers. Cervix was dilated through fanning and fathering. A dead male calf was relieved through mutational operations. Fetal fluids were drained slowly. After draining the fluids animal is administered with fluids and advised for antibiotic therapy for 3 days. Animal had uneventful recovery.